Whole genome diversity of inherited chromosomally integrated HHV-6 derived from healthy individuals of diverse geographic origin - Telford, Marco (Sci Rep, 2018)
Human herpesviruses 6-A and -B (HHV-6A, HHV-6B) are ubiquitous in human populations worldwide. These viruses have been associated with several diseases such as multiple sclerosis, Hodgkin’s lymphoma or encephalitis. Despite of the need to understand the genetic diversity and geographic stratification of these viruses, the availability of complete viral sequences from different populations is still limited. Here, we present nine new inherited chromosomally integrated HHV-6 sequences from diverse geographical origin which were generated through target DNA enrichment on lymphoblastoid cell lines derived from healthy individuals. Integration with available HHV-6 sequences allowed the assessment of HHV-6A and -6B phylogeny, patterns of recombination and signatures of natural selection. Analysis of the intra-species variability showed differences between A and B diversity levels and revealed that the HHV-6B reference (Z29) is an uncommon sequence, suggesting the need for an alternative reference sequence. Signs of geographical variation are present and more defined in HHV-6A, while they appear partly masked by recombination in HHV-6B. Finally, we conducted a scan for signatures of selection in protein coding genes that yielded at least 6 genes (4 and 2 respectively for the A and B species) showing significant evidence for accelerated evolution, and 1 gene showing evidence of positive selection in HHV-6A.